Dimensi Teologis dan Logis dalam Pemahaman Syukur: Studi pada Kitab Tafsir Fī Ẓilāl al-Qur’ān oleh Sayyid Quṭb (l. 1906) - Aulul Azmi (Asosiasi Ilmu Alquran dan Tafsir se-Indonesia, 2023)
This study examines the concept of gratitude (syukur) in Sayyid Quṭb's (1906 CE) tafsir Fī Ẓilāl al-Qur’ān, which integrates theological and logical aspects in its interpretation. The research employs content analysis with a qualitative approach, focusing on Quṭb's interpretations of Quranic verses related to gratitude. The primary data sources are the tafsir Fī Ẓilāl al-Qur’ān and related literature discussing Quṭb’s thought. The findings reveal that Quṭb provides a comprehensive understanding of gratitude encompassing theological, cognitive, and philosophical dimensions. He emphasizes that gratitude is not merely a verbal expression or ritual worship but also involves human awareness of free choice and the logical consequences of their actions. This research fills a gap in previous studies that have often overlooked an in-depth analysis of the concept of gratitude in Quṭb’s tafsir and contributes significantly to understanding how the Quran connects theological and logical dimensions within the context of human life.